364 Disabling farm injuries and safety interventions: an indian study. (1st September 2016) - Kumar, Adarsh; Singh, JK
Abstract : Background: 260 million perons are associated with farm activities in India. Aaccording to Census 2011, a total of 26.8 million persons are disable. There is an increase of 5 million in last 10 years, indicating an addition of 1400 disabled individual every day. In agricultural "acquired disability" because of unsafe farm machine injuries is an added dimension to rural disability. Methods: Compensation data of agricultural injury victims (156 cases) were collected from the Sonipat District, Haryana, India to assess kind of injuries and disabilities along with machines associated for the years 2008 to 2014. The most common machines associated with disabling injury was fodder cutter, safety interventions were developed and retrofitted in 50 households and feedback was collected. Results: Total bodily injuries were 105 out of 156 cases, out of which 84 cases (80%) pertains to amputation of fingers, 13 cases involved and wrist (12%), 5 cases (5%) had leg injury, one person (1%) injured his eye and four cases (4%) injuries sustained on upper body. Machines associated with injuries were chaff cutters (74 cases), electric motors (20 cases), tube wells (6 cases), threshers (12 cases), tractor/trolley (9 cases), harrows (2 cases), and one each of reaper, sickle, winnower, and seed drill. The causal factor associated with fodder cutter injuries were; accessibility of children to machine, get injured while playfully interacting with this machine; hands injuries while feeding the fodder as entrapped in the rollers; diverted attention; loose clothes, get entangles in the gears and belt. Conclusions: Simple safety gadgets consisting of blade guard, flywheel lock, warning roller were developed and retrofitted in rural households and feedback suggested that it prevents injuries but some farmers of the opinion that warning roller hinders feeding of fodder quickly.